First serodetection and molecular phylogenetic documentation of Coxiella burnetii isolates from female camels in Wasit governorate, Iraq - Mawlood A. Al-Graibawi; Afaf A. Yousif; Hasanain A. Gharban; Jakob Zinsstag (Iraqi Journal of Veterinary Sciences, 2021)
This study aims to detect Coxiella burnetii in one-humped female camels (Camelus dromedarius) using ELISA and confirmation of infection by PCR with the phylogenetic analysis of local isolates. The 91 adult female camels were selected for clinical examination and blood sampling from different areas in Badra and Al-Numaniyah districts in Wasit governorate, Iraq, from February to April 2019. The prevalence of Coxiella(C.) burnetii was 19.8% and 4.4% by ELISA and PCR, respectively. Targeting 16S rRNA genes from three positive samples were documented in the Genbank-NCBI under accession numbers of MN900579.1, MN900580.1, and MN900581.1. Clinical evaluation revealed insignificant variation in temperature, pulse, respiratory rates, and lymph node enlargement among the positive and negative animals. The findings also showed that camels of the Badra regions have positive signs. burnetii compared to other regions, and the infection was increased significantly in April and March. In conclusion, our findings confirmed the prevalence of C. burneth among Iraqi female camels, suggesting that these animals might be a source of the pathogen for humans and other animal species. Therefore, further studies are necessary to provide more detailed data about the prevalence of C. burnetiito to improve effective control measures.